Investigation on the Height Calculation of Water Flowing Fracture Zone during Coal Mining under Ordovician Limestone Nappe Aquifer - Chengcheng Chu (Advances in Civil Engineering, 2022)
This paper focused on the height calculation of water flowing fracture zone during mining under the Ordovician limestone nappe aquifer. According to the critical conditions of crack arresting under the action of compression-shear stress, a formula for calculating the height of water flowing fracture zone during mining under the Ordovician limestone nappe aquifer was proposed, which takes tectonic stress, the influence of fault, the mechanical effect of the seepage field on the stress field, and the rock softening with water into consideration. The formula was applied to calculate the height of water flowing fracture zone above panel E3213 in the first eastern mining area of the Qianyingzi coalmine. The comparison between the theoretical calculation and the measured result shows that the formula proposed in this paper is closest to the measured value and further improves the calculation accuracy compared with the previous formulas. This study not only has important theoretical and practical significance for the safe mining of Qianyingzi coalmine, but also has important theoretical and practical significance for the coalmine facing the double threat of Ordovician limestone confined aquifer and reverse fault.